The impact of input quality on early sign development in native and no n-native language learners - Lu, Jenny; Jones, Anna; Morgan, Gary (Journal of Child Language, 2016)
There is debate about how input variation influences child language. M ost deaf children are exposed to a sign language from their non-fluent hearing parents and experience a delay in exposure to accessible lang uage. A small number of children receive language input from their dea f parents who are fluent signers. Thus it is possible to document the impact of quality of input on early sign acquisition. The current stud y explores the outcomes of differential input in two groups of childre n aged two to five years: deaf children of hearing parents (DCHP) and deaf children of deaf parents (DCDP). Analysis of child sign language revealed DCDP had a more developed vocabulary and more phonological ha ndshape types compared with DCHP. In naturalistic conversations deaf p arents used more sign tokens and more phonological types than hearing parents. Results are discussed in terms of the effects of early input on subsequent language abilities.